When Life Hangs by a Thread: Representations of Covid-19 by the Mapula Embroidery Project. (2nd January 2023) - Schmahmann, Brenda
Abstract: In 2020, the Mapula Embroidery Project were commissioned to produce a series of 14 artworks in cloth on the topic of Covid-19 and its impact on their community. However, as the article reveals, the relationship of the works to the actual lived experiences of project members turned out to be complex, indirect or even paradoxical. In their choice and treatment of subject matter, members of the project sometimes represent their aspirations rather than necessarily their difficulties. While sometimes exposing hardships people experience or illustrating their own fears, they also often represent scenarios that are suggestive of an aspiration to be part of an ordered society where difficulties are overcome. Furthermore, while the works include imagery drawn from designers' own perceptions of their everyday environment, they also at times incorporate motifs and text gleaned from online searches and television broadcasts, in effect recording messages and discourses about Covid-19 current at a particular historical juncture. Consequently, while not literal reflections of practices in the context of the pandemic, the cloths have an important "truth" value: they invoke people's fears and anxieties while also suggesting their capacity to sustain hope in a time of challenge and uncertainty.